The presence of marin Pliocene sendiments in the Mesohellenic Trough (Pramoritsa banks, Grevena, Greece) - ΦΟΥΝΤΟΥΛΗΣ, Ι.; ΜΑΡΚΟΠΟΥΛΟΥ-ΔΙΑΚΑΝΤΩΝΗ, Α.; ΜΠΑΚΟΠΟΥΛΟΥ, Α.; ΜΩΡΑΪΤΗ, Ε.; ΜΙΡΚΟΥ, Μ. Ρ.; ΣΑΡΟΓΛΟΥ, Χ. (Bulletin of the Geological Society of Greece, 2018)
Detailed lithostratigraphic study of the postalpine deposits that build Pramoritsa river banks - tributary of Aliakmonas river- north of Grevena (Greece), showed that the marine molassic deposition did not cease in the Upper Miocene but continued in the Lower Pliocene, too. Systematic sampling revealed abundant pelagic and benthic fossils, the presence of which {Bulimina exilis, Bulimina costata, Neogloboquadrina acostaensis, Globigerinella pseudobesa, Globoquadrina venezuelana, Neoeponides schreibersii, Pulleniatina obliquiloculata, Dorothia gibbosa) proves that marine facies went on, at least, until the Lower Pliocene and that the depositional environment was characterized as coastal with warm waters. According to the Nannoplankton flora correlated with standard nannoplankton -zones-subzones NNllb Amaurolithus delicatus, Discoaster quinqueramus) and NN13 (Ceratolithus rugosus) of MARTINI, 1971 and OKADA & BUKRY, 1980 during the Late Miocene -Early Pliocene. Besides, some characteristics of the Pliocene sediments are described, based on macro- and microscopic observations.